Hubungan Antara Project-Based Learning dan Kemampuan Berbicara Dalam Bahasa Inggris Untuk Siswa Sekolah Menengah Atas - maqbulin, arjunina (Inovasi: Jurnal Diklat Keagamaan, 2023)
Nowadays, students are taught to achieve the skills that will help them to survive in the 21st century. The important skills that students should master to face the 21st century are critical thinking, problem-solving, communication, and collaboration. One of the models that can be used to prepare the students to face it is Project-based learning. While for teaching English, this model can be used especially for productive skills such as writing and speaking. In project-based learning, students work in groups to finish the project, while in improving speaking skill, students will also learn better when they practice in a group because students will speak better when they enjoy the activity. As both Project-based learning and speaking ability are applied better in the group, that is why it is important to correlate between project-based learning and students' speaking ability. This research aims to answer the research question of whether there is the relationship between Project-based learning and Students' speaking ability. Therefore, correlational research is used. The sample used in this research is the students of the eleventh science 1 grade, that consists of 36 students. The instruments to collect the data are a questionnaire to know the grade of Project-based learning and a speaking test to know the students' speaking ability. This research shows that the Pearson correlation value between Project-based learning and speaking skill is 0,107, which means there is a very weak correlation between project-based learning and speaking skills. In addition, the result also means that there is no statistically significance value between project-based learning and speaking skills as the significance value is 0,534 which is bigger than 0,05 (0,534 > 0,05).